THE ANALYSIS IS FOR THE DESIGN OF DIFFERENT CLUB FACE’S THICKNESSES OF FAIRWAY WOOD TO THE CHARACTERISTIC TIME - Kueipin Kuo (Universitas Diponegoro, 2020)
Background: The main factors to influence on the stroking performance of club head are alloy and spring-like effect. Design the structure of new club face to create the fairway wood which can show best stroking feeling and let driving distance become longer. Purpose: The club face of fairway wood is processed through the iron alloy heating procedure and CNC to innovate the club head with high spring-like effect (characteristic time). Method: (1) Use 455 stainless steel processed by heating and aging treatment, to do the analysis on microstructure and mechanical properties. (2) Through CNC to design seven different patterns for the back of club face, each pattern for three club head. The total amount is twenty-one. (3) Make finished product be test the characteristic time and the ability of strike by the practical measurement. (4) To analyze after the compare between three-way ANOVA and LSD. Results: After 455 stainless steel was heated in procedure S850℃-A550℃, mechanical properties became superior and had the better malleability, it is suitable for developing the club face of high spring-like effect. Before and after grinding among three-way ANOVA (pattern*thickness*place), did not achieve the significant level on the figure of characteristic time. Through two-way ANOVA (pattern*place and thickness*place), showed the significant deviation before and after grinding. After doing the crash test by 45m/s, all the results can reach the higher limited standard. Summary: 455 stainless steel was designed with the different club face’s thicknesses of fairway wood can make spring-like effect achieve high characteristic time. The much thinner club face let the characteristic time perform highly. But there was no obvious effects from the patterns of the back club face.